Resection and primary anastomosis with or without modified blow-hole colostomy for sigmoid volvulus - Coban, Sacid (The WJG Press and Baishideng, 2008)
AIM: To evaluate the efficacy of resection and primary anastomosis (RPA) and RPA with modified blow-hole colostomy for sigmoid volvulus. METHODS: From March 2000 to September 2007, 77 patients with acute sigmoid volvulus were treated. A total of 47 patients underwent RPA or RPA with modified blow-hole colostomy. Twenty-five patients received RPA (Group A), and the remaining 22 patients had RPA with modified blow-hole colostomy (Group B). The clinical course and postoperative complications of the two groups were compared. RESULTS: The mean hospital stay, wound infection and mortality did not differ significantly between the groups. Superficial wound infection rate was higher in group A (32% vs 9.1%). Anastomotic leakage was observed only in group A, with a rate of 6.3%. The difference was numerically impressive but was statistically not significant. CONCLUSION: RPA with modified blow-hole colostomy provides satisfactory results. It is easy to perform and may become a method of choice in patients with sigmoid volvulus. Further studies are required to further establish its role in the treatment of sigmoid volvulus.